The Function Of Tag Questions In Sudanese Females’ Interaction - Tabidi, Muna Babiker (Advances in Social Sciences Research Journal, 2017)
The goal of my study is to investigate the use of ‘tag questions’ in Sudanese women’s conversations. The main assumption is that Sudanese women’s linguistic behavior, with respect to tag questions, has a role to play in creating co-operation and intimate social relationships among them. The analysis of the present study based on recordings of naturally occurring talk among women friends in Khartoum. The participants were forty-one women from different age groups and educational levels. The total period of the recorded data was twenty-three hours. The study used three hours transcribed talk in the process of data analysis. Following Jefferson’s transcription system, the data have been transcribed, transliterated, and translated into English. I adopted Conversation Analysis approach in analyzing the data. The results of this research show that the subjects tended to use tag questions in their private conversations. The women in the sample adopted this linguistic device to co-operate in completing communicative tasks during natural interactions, enhancing solidarity and good social relations among them.